2015
DOI: 10.1007/s11357-015-9773-1
|View full text |Cite
|
Sign up to set email alerts
|

C57BL/6 life span study: age-related declines in muscle power production and contractile velocity

Abstract: Quantification of key outcome measures in animal models of aging is an important step preceding intervention testing. One such measurement, skeletal muscle power generation (force * velocity), is critical for dynamic movement. Prior research focused on maximum power (Pmax), which occurs around 30–40 % of maximum load. However, movement occurs over the entire load range. Thus, the primary purpose of this study was to determine the effect of age on power generation during concentric contractions in the extensor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
58
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 62 publications
11
58
1
Order By: Relevance
“…This finding is consistent with studies which report that power output is affected with age earlier than other performance outcomes such as static performance (i.e. isometric force) [20][21][22] . Rats at 3 months of age were in a late adolescent state of maturation as confirmed by 5% shorter tibia lengths and 24% lower body weights relative to those of 6 month old rats.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with studies which report that power output is affected with age earlier than other performance outcomes such as static performance (i.e. isometric force) [20][21][22] . Rats at 3 months of age were in a late adolescent state of maturation as confirmed by 5% shorter tibia lengths and 24% lower body weights relative to those of 6 month old rats.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, in hamsters, aging decreased diaphragm maximal shortening velocity and peak power [89]. Ongoing studies by our group suggest that diaphragm bundles from mice in advanced stages of aging (30 mo old, <50% survival rate) also show decreases in maximal shortening velocity and peak power [90], which are consistent with those seen in limb muscles [91,92]. Thus, impairments in diaphragm isotonic contractile properties may have a delayed onset and be more relevant in very old age.…”
Section: Intrinsic Diaphragm Muscle Abnormalitiesmentioning
confidence: 62%
“…This was particularly the case for comparison of myofiber CSA and absolute muscle mass, which suggested minimal differences between the young and aged mice. Other investigators have also observed that C57BL/6 mice show relatively mild changes in muscle at 24 months [ 32 , 33 ]. Interestingly, despite the lack of difference in absolute gastrocnemius muscle mass and findings of similar muscle fiber size, the aged mice demonstrated reduced muscle function on grip and during in situ twitch force testing.…”
Section: Discussionmentioning
confidence: 93%